2021
DOI: 10.3390/ijerph18042002
|View full text |Cite
|
Sign up to set email alerts
|

A Typology of Poles’ Attitudes toward COVID-19 during the First Wave of the Pandemic

Abstract: (1) Objective: To explore Poles’ attitudes during the first wave of COVID-19 pandemic in 2020 as a contribution toward the creation of effective health policies. (2) Method: Computer-assisted web interviewing (CAWI) was used to survey a sample of 1001 Poles selected using quota sampling. (3) Results: Using cluster analysis, three types of attitudes were distinguished, people being classified as “involved” (48.1%), “cautious” (27.4%), or “indifferent” (24.6%). The result of greatest interest was the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…As the results show, females tend to regard these over-prevention behaviors as correct measures. It may because they perceive a higher epidemic risk and greater vulnerability than males, as Boguszewski et al suggested in their study [ 37 ]. Besides, we found that staffs working in institutions have the most proper cognition of excessive behaviors in Factor 1 that directly and greatly damage personal health.…”
Section: Discussionmentioning
confidence: 96%
“…As the results show, females tend to regard these over-prevention behaviors as correct measures. It may because they perceive a higher epidemic risk and greater vulnerability than males, as Boguszewski et al suggested in their study [ 37 ]. Besides, we found that staffs working in institutions have the most proper cognition of excessive behaviors in Factor 1 that directly and greatly damage personal health.…”
Section: Discussionmentioning
confidence: 96%
“…The second approach focuses on analysing the COVID-19 epidemic affecting the territories of individual countries or parts of the world [2,[29][30][31][32][33][34]. From the research area's point of view, studies on the COVID-19 epidemic in Poland are important [35][36][37][38][39][40], especially in cities and an environment conducive to infections [41]. There is still insufficient research in this area.…”
Section: Research Reviewmentioning
confidence: 99%
“…The COVID-19 mortality rate was 2.2% [19]. In June 2020, around 820 people per million inhabitants had been diagnosed as infected, as compared with the following numbers of cases per million in other countries: USA, 6900; Belgium, 5200; UK, 4400; Italy, 3900; but only 280 in neighboring Slovakia [20].…”
Section: Introductionmentioning
confidence: 97%